Implementing the UN Declaration on the Rights of Indigenous Peoples: Handbook for Parliamentarians N° 23 - IPU, OHCHR; UNDP, UNDESA; IFAD (2014)
This handbook is divided into two sections. The first section focuses on questions concerning indigenous peoples such as: why indigenous peoples’ rights are important for parliamentarians; who are indigenous peoples; what are indigenous peoples’ rights under international standards; what is free, prior and informed consent, and why free, prior and informed consent is important for parliamentarians